Evaluación clínica del paciente con síntomas del tracto urinario inferior - Valdevenito S., Juan Pablo; Álvarez O., Diego; Kobus G., Cristóbal; Bull C., Leonardo (Revista Hospital Clínico Universidad de Chile, 2016)
Lower urinary tract symptoms are divided into three groups, storage, voiding and post micturition symptoms. Their level of agreement with urodynamic investigation is poor. Clinical history should be complemented by the application of validated symptom questionnaires and the recording of urinary events. Here we refer to: a) the International Consultation on Incontinence Questionnaire, Short Form (ICIQ-SF), b) the Urogenital Distress Inventory - Short Form (UDI-6) and Incontinence Impact Questionnaire – Short Form (IIQ-7), c) the urinary incontinence Severity Index and d) the American Urological Association Symptom Index. The recordings of urinary events can be done in three main forms: a) micturition time chart, b) frequency volume chart, and c) bladder diary. The International Consultation on Incontinence Questionnaire bladder diary (ICIQ bladder diary) is the only one validated. Physical exam should include abdominal and genital examination, covering pelvic organ prolapse quantification in women, prostate evaluation in men, pelvic floor muscle function evaluation in both genders, and a neurologic examination focused on evaluation of the sacral nerves. It is useful to supplement the physical examination with the evaluation of the mobility of the bladder neck and proximal urethra through the Q-tip test, and with the quantification of urine leakage through the pad test